Evaluation of a distractor to increase joint space of the stifle joint in dogs: a cadaveric study - Rovesti, G. L.; Devesa-Garcia, V.; Urrutia, P. G.; San Roman, F.; Rodriguez-Quiros, J. (Veterinary and Comparative Orthopaedics and Traumatology, 2015)
Objective: To evaluate the technical feasibility and efficacy of a joint distraction technique to increase the stifle joint space and assess potential soft tissue damage due to the distraction.Methods: Twenty stifle joints of twelve canine cadavers without evidence of disease were radiographically evaluated by medio-lateral, cranio-caudal and varus-valgus stressed projections. Joint distraction was applied with loads from 40 N up to 200 N, and the joint space achieved was measured on radiographic images. Distraction plus distension with saline was subsequently applied and measured. Varus-valgus stressed projections were repeated after distraction to evaluate a potential increase in joint laxity.Results: Distraction produced a significant increase of the joint space for most of the evaluated loads. Distraction plus distension produced a significant increase for most of the loads compared to the distraction alone. No ensuing joint laxity could be inferred from the post-distraction radiographic evaluation.Clinical significance: Stifle distraction produces an increase of the joint space, which is wider when intra-articular saline is injected. This may be potentially useful for improving joint structure visualization and facilitating arthroscopic procedures, thus reducing the potential for iatrogenic damage to intra articular structures. No soft tissue damage could be inferred by radiographic pre- and post-procedure comparison. Further clinical studies are required to evaluate potential neurovascular complications.
Keywords: Stifle joint; joint distraction; arthroscopy; traction stirrup; dog